Adverse Effects of Pain Medication Used in Sport Medicine - Kubicki, Mateusz; Hebda, Patryk; Cemaga, Roman; Błaszkowski, Bartłomiej; Wolski, Adam; Król, Maria; Pustuła, Paweł; Szplit, Ewa; Czapliński, Mieszko; Michnowska, Wiktoria (Quality in Sport, 2026)
Background: Acute and chronic pain is a very common problem amongst people involved in sports, whether professionally or recreationally. Most of them require the use of medication in order to alleviate the pain. Extensive use of pain medication is burdened with an increased risk of adverse effects. Aim: The aim of this narrative review is to summarise the adverse effects of the most popular pain management medication currently in use in sport medicine. Material and methods: A comprehensive literature review was conducted via the advanced research tool in PubMed in order to find eligible and relevant articles regarding pain medication and their adverse effects. Results: Extensive intake of NSAIDs in high doses increases the risk of gastrointestinal bleeding. The greatest concern regarding the use of paracetamol is its hepatotoxicity. Antidepressants are characterised by a wide variety of adverse effects, such as hypertension, dry mouth, constipation, and an increased risk of falls. The most common adverse effects of gabapentinoids are somnolence, fatigue, and dizziness. Conclusions: Most injuries experienced by athletes can be managed with NSAIDs, acetaminophen, and weak oral opioids prescribed for a short period of time, whereas chronic pain treatment should start with TCAs, SNRIs, or gabapentinoids. Prolonged intake of pain medication increases the risk of the occurrence of serious adverse effects. Physicians ought to monitor their patients and act accordingly should any adverse effects occur.